Gambaran Hemoglobin pada Pendonor yang Ditolak di PMI Tahun 2020-2021 dan Faktor yang Mempengaruhi - Hendar Fahmi Ananda; Miftahur Rizqiya Sekar Jati; Dinda Ayu Mustika Putri; Husna Azia; Zainul Akbar; Rodhi Hartono (Poltekkes Kemenkes Semarang, 2023)
Hemoglobin or Hb is a protein found in red blood cells. This protein is what makes blood red. In normal levels, hemoglobin has many functions for the body, so normal levels of hemoglobin need to be maintained. In addition to giving color, hemoglobin also functions to help red blood cells get their natural shape, which is round with a flatter center. With this shape, red blood cells can easily move and flow in the blood vessels. Based on the Regulation of the Minister of Health Number 91 of 2015 the normal level of hemoglobin before blood donation is 12.5 - 17.0 gr/dL%. When a person's hemoglobin condition is higher or lower than the normal amount, this can be a sign of a health problem.